An ultrastable laser system at 689 nm for cooling and trapping of strontium - Qiao, Chang; Zhu, Bing; Weidemüller, Matthias (Applied physics. B, Lasers and optics, 2019)
We present a 689-nm cavity-based laser system for cooling and trapping strontium atoms. The laser is stabilized to a high-finesse cavity by the Pound-Drever-Hall technique, exhibiting a frequency stability in the 10−1410−1410^{-14} range for averaging times up to 100 s. A cavity drift of 8 kHz per day is mapped out and compensated. At short times, the laser exhibits a linewidth of a few kilohertz. With this laser system, we realize a magneto-optical trap of strontium operated on the narrow inter-combination transition yielding sub-microkelvin temperatures, and demonstrate absorption spectroscopy on the strontium inter-combination line.
Gesehen am 04.12.2019